2013
DOI: 10.11648/j.ajep.20130206.17
|View full text |Cite
|
Sign up to set email alerts
|

Modified Activated Carbon and Bentonite Used to Adsorb Petroleum Hydrocarbons Emulsified in Aqueous Solution

Abstract: Adsorption is one commonly used technique for treatment of petroleum contaminated water. This study aims to modify the adsorption surface of bentonite clay and activated carbon as organoclay and acid modified activated carbon, respectively. The modified and unmodified adsorbents were characterized by analysis of specific surface area, cation exchange capacity and point of zero charge (pH pzc). Furthermore, adsorbents efficiencies were evaluated in the adsorption of petroleum hydrocarbon from oil-water emulsion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 21 publications
0
27
1
Order By: Relevance
“…In recent years, the modification of the surface of minerals with surfactants from the group of quaternary ammonium salts has become a very popular field of research [52][53][54][55][56]. This kind of functionalization changes the character of a mineral materials' surface from hydrophilic to hydrophobic, which usually increases the affinity of the sorbent for organic pollutants.…”
Section: Modified Mineral Adsorbentsmentioning
confidence: 99%
“…In recent years, the modification of the surface of minerals with surfactants from the group of quaternary ammonium salts has become a very popular field of research [52][53][54][55][56]. This kind of functionalization changes the character of a mineral materials' surface from hydrophilic to hydrophobic, which usually increases the affinity of the sorbent for organic pollutants.…”
Section: Modified Mineral Adsorbentsmentioning
confidence: 99%
“…In recent years, intense researches have been performed to improve the AC selectivity for adsorbing specific contaminates by improving the carbon surface through different chemical, physical and biological methods (Bhatnagar et al 2013). The number of acidic functional groups on the AC surface is related to uptake of organic contaminants (Emam 2013). The acidic character of AC is attributed to oxygen containing surface groups (i.e., carboxyl, carbonyl and phenols) on the outer surface or edge of the basal AC plane (Shafeeyan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The acidic character of AC is attributed to oxygen containing surface groups (i.e., carboxyl, carbonyl and phenols) on the outer surface or edge of the basal AC plane (Shafeeyan et al 2010). Emam (2013) investigated the effect of AC acidic treatment on oil sorption from water at pH 7, which oil sorption was increased up to 12 mg in comparison with untreated AC.…”
Section: Introductionmentioning
confidence: 99%
“…Ksiezopolska and Pazur (2011) reported that the specific surface area of bentonite and illite reduced after complexion with humic acids at all pH values as a result of lodged humic acid in the active sites on clays and making the surface of the complex hydrophobic. Whereas, in surfactant modified bentonite the interparticle pores are covered and clogging of the interlayer space by HDTMA molecules prevented the N 2 access to the inner surface of material Erdem et al, 2010;Emam 2013). …”
Section: Physicochemical Properties Of Adsorbentsmentioning
confidence: 99%